Marketing Influencer, Price, and Product Quality Factors That Influence The Purchase Decision Of G2G (Glad2glow) Products on Tiktok Shop (A Study on Tiktok Shop Glad2glow_indo Followers) - Naibaho, Esrawati; Nurmulya, Fitrasyah (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
This study aims to analyze the influence of marketing influencer, price, and product quality towards the purchase decision of G2G (Glad2Glow) products on the TikTok platform. The method used is quantitative with a survey approach to 100 respondents who are followers of the Glad2Glow_Indo TikTok shop account. Data was collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS V.25. The results of this study indicate that influencer marketing, price, and product quality have a positive and significant influence on purchasing decisions. The results of this study indicate that influencer marketing has a positive and significant influence on purchasing decisions with a coefficient of 0.167 and a Sig. value of 0.009. Price has a positive and significant influence on purchasing decisions with a coefficient of 0.297 and a significance value of 0.001. Product quality has a positive and significant influence on purchasing decisions with a coefficient of 0.193 and a significance value of 0.015. Simultaneously, all three variables have a significant influence on purchasing decisions. With an F value of 37.725 and a significance level of 0.000, which is less than 0.05.